Analysis of Machine Learning Methods Using Spam Filtering - Boyko, Nataliya; Dypko, Oleksandra (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2021)
The paper considers methods of the naive Bayesian classifier. Experiments that show independence between traits are described. Describes the naive Bayesian classifier used to filter spam in messages. The aim of the study is to determine the best method to solve the problem of spam in messages. The paper considers three different variations of the naive Bayesian classifier. The results of experiments and research are given.